2012
DOI: 10.5194/aab-55-163-2012
|View full text |Cite
|
Sign up to set email alerts
|

The use of a lesion score as an indicator for agonistic behaviour in pigs

Abstract: The aim of the present study was to analyse whether a lesion score approach could be used as an indicator for agonistic behaviour in pigs. Behavioural patterns were observed directly after weaning (PIG-28, n=827), 40 days later (growing pigs, PIG-68, n=292) and immediately after mixing gilts (GILTS, n=344), over a 48 h period. For the front, middle and rear part of the body the extent of skin injuries was assessed with a lesion score (LS). The LS ranked from 0 (no wounds) to 4 (many, deep wounds) and was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Lesion scores have been used in previous studies to determine the aggression level of pigs [20]. Hodgkiss et al [20] and Stukenborg et al [32] demonstrated that the severity, duration and frequency of overt aggression or fighting can be estimated by looking at the number of scratches or injuries on pigs, especially injuries to the anterior region of their body. However, aggression is also influenced by factors such as the familiarity of pigs, space allowance, group size and composition, pen design, time of day, food and bedding [33].…”
Section: Discussionmentioning
confidence: 99%
“…Lesion scores have been used in previous studies to determine the aggression level of pigs [20]. Hodgkiss et al [20] and Stukenborg et al [32] demonstrated that the severity, duration and frequency of overt aggression or fighting can be estimated by looking at the number of scratches or injuries on pigs, especially injuries to the anterior region of their body. However, aggression is also influenced by factors such as the familiarity of pigs, space allowance, group size and composition, pen design, time of day, food and bedding [33].…”
Section: Discussionmentioning
confidence: 99%
“…Skin lesions on the body of all pigs were registered by the same observer in the home pen before transport and after the second blood sampling essentially as described 61 . The total number of lesions was evaluated in home pen and after transport.…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate counting, the body was divided into three regions: head, neck and shoulder region, and the remaining parts of the body. Recordings were done only on fresh lesions, which were judged subjectively by colour and the estimated age of scabbing ( Turner et al, 2006 ).The scoring method used followed that of Stukenborg et al (2012) . To keep the scores consistent throughout the experiment, one person assessed the injury scores.…”
Section: Methodsmentioning
confidence: 99%